SDF‐1‐edited human amniotic mesenchymal stem cells stimulate angiogenesis in treating hindlimb ischaemia. Issue 13 (26th May 2022) - Zhang, Hong Zhe; Han, Seongho; Kim, Sung‐Whan
Abstract: Although stem cells have extensively been studied as a novel vehicle for tissue repair, their sustained efficacy remains controversial. In this study, we aimed to investigate the angiogenic potency over time of stromal cell‐derived factor‐1 ( SDF‐1 ) gene‐edited amniotic mesenchymal stem cells (AMM/S) in a hindlimb ischaemia model. An SDF‐1 transgene was inserted into the AMM cell genome via transcription activator‐like effector nuclease (TALEN) mediated knock‐in, and cell migration, Matrigel tube formation, and in vivo Matrigel plug assays were performed. AMM/S were also transplanted into hindlimb ischaemia model mice. Blood perfusion, therapeutic potential, histology, capillary density and in vivo angiogenic assays were performed. AMM/S exhibited high expression of the SDF‐1 gene, and robustly promoted migration, proliferation and microvascular formation. AMM/S transplantation significantly increased blood perfusion and limb loss prevention compared with AMM. AMM/S also significantly inhibited increased capillary density and expression of angiogenic factors in the ischaemic hindlimb. Our study demonstrated that AMM/S provides a significant therapeutic effect in ischaemic hindlimbs by enhancing angiogenesis.